Marketing Mix Architecture for forest Products: Focus on Azadirachta indica (Neem) - Rastogi, Alind (Indian Forester, 1995)
The Non-Timber Forest Products (NTFPs) have immense role in shaping the rural economy in India. With the changing forest management profile in favour of eco-friendly products and participatory management of forest areas, the NTFPs can have valuable contribution. Neem has an important place in utility canvass be it medicine, pesticide or bio-fertilizer. Suitable marketing efforts are needed to realise its true economic potential. The paper discusses the marketing mix architecture in favour of Neem as a desired effort on the part of forest managers and researchers.